Samoregulacija gospodarskih razmerij in Obligacijski zakonik - Grilc, Peter (Pravni letopis, 2012)
The paper deals with the concept and importance of self-regulation and autonomous legal sources of commercial law, particularly contract law and the banking sector. It deals with several topics: (i) whether the Obligation Code in terms of self-regulation is appropriate and modern, (ii) whether the deletion in Law of obligations regulated banking chapters in appropriate way, (iii) whether the aspects of self-regulation or modern complex contracts, such as leasing, franchising, factoring may be considered as adequate substitute legal sources, (iv) whether the extent to which self-regulation and autonomic regulation of banking business practices replaced nonexistent provisions of the Obligation Code or other parts of the commercial contracts. The autonomy and self-control approach increase the capacity of the business sector. Both of them are considered as complementary legal sources and they are not considered as substitute for regulation and part of the strategy of the state (regulating smarter). Self-regulation and autonomy cannot be considered as a tool for reducing concern for safety, the environment and important values.
Keywords: autonomy; avtonomija; bančništvo; gospodarsko pravo; obligacijsko pravo; pogodbe; pogodbeno pravo